Effects of dietary Yucca meal on growth, haematology, non‐specific immune responses and disease resistance of juvenile Nile tilapia, Oreochromis niloticus (Linnaeus, 1758). (22nd February 2017) - Njagi, Grace W; Lee, Seunghan; Won, Seonghun; Hong, Jeongwhui; Hamidoghli, Ali; Bai, Sungchul C
Abstract: A 10‐week feeding trial was conducted to determine the effects of dietary yucca meal supplementation on growth, haematology, non‐specific immune responses and disease resistance in juvenile Nile tilapia, Oreochromis niloticus . Six isonitrogenous and isoenergetic experimental diets were formulated to contain 0% (YMS0 ), 0.1% (YMS0.1 ), 0.3% (YMS0.3 ), 0.5% (YMS0.5 ), 1% (YMS1.0 ) and 2% (YMS2.0 ) dietary yucca meal on the dry weight basis. Results of this study showed a higher growth performance for YMS0.1 group with significant differences with YMS0.5, YMS1.0 and YMS2.0 groups. In addition, whole‐body protein content of fish fed the YMS0.1 diet was significantly higher as compared to YMS0 . Plasma lysozyme activity significantly increased in YMS0.1 group comparing to YMS0 and YMS0.5 groups. Respiratory burst activity of phagocytic blood cells was significantly enhanced when fish were fed the YMS0.1 diet. Results also showed that yucca meal supplementation had moderate effects on glutamic oxaloacetic transaminase and cholesterol levels. After the 14‐day challenge test with Aeromonas hydrophila, cumulative survival of fish fed YMS0.1 diet was significantly higher than that of fish fed diet YMS0, YMS1.0 and YMS2.0 . These results suggest that the optimum dietary yucca meal inclusion level in the diet of juvenile Nile tilapia could be between 0.1% and 0.14% (23.9~33.4 mg kg −1 saponin) as a feed additive to promote growth, enhance the non‐specific immune responses and increase disease resistance.